2021
DOI: 10.1093/ageing/afab131
|View full text |Cite
|
Sign up to set email alerts
|

Orthopaedic physiotherapists’ perceptions of mechanisms for observed variation in the implementation of physiotherapy practices in the early postoperative phase after hip fracture: a UK qualitative study

Abstract: Objective to explore physiotherapists’ perceptions of mechanisms to explain observed variation in early postoperative practice after hip fracture surgery demonstrated in a national audit. Methods a qualitative semi-structured interview study of 21 physiotherapists working on orthopaedic wards at seven hospitals with different durations of physiotherapy during a recent audit. Thematic analysis of interviews drawing on Normalis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(55 citation statements)
references
References 31 publications
4
45
0
Order By: Relevance
“…In accordance with reported sources of variation, we found that the main determinants of optimal rehabilitation were organisational features [17,18,23,24] and engagement of patients, carers and the multidisciplinary team [17][18][19][20][21][22][23][24]. For these to be addressed, the presence of supportive management and leadership often stood out as essential to promote a positive culture where multidisciplinary teams, adequately trained and supported, communicated and worked well together towards person-centred goals.…”
Section: Main Findingssupporting
confidence: 81%
See 4 more Smart Citations
“…In accordance with reported sources of variation, we found that the main determinants of optimal rehabilitation were organisational features [17,18,23,24] and engagement of patients, carers and the multidisciplinary team [17][18][19][20][21][22][23][24]. For these to be addressed, the presence of supportive management and leadership often stood out as essential to promote a positive culture where multidisciplinary teams, adequately trained and supported, communicated and worked well together towards person-centred goals.…”
Section: Main Findingssupporting
confidence: 81%
“…Particularly believed as detrimental for recovery outcomes was patients not taking ownership for their own rehabilitation journey. The importance of this responsibility has been priorly reported for this patient population [17,23]. In accordance, this and other studies state health professional's role on informing, educating, and encouraging patients and carers [17,[19][20][21][22][23][24].…”
Section: Barriers To Optimal Rehabilitationsupporting
confidence: 79%
See 3 more Smart Citations